Truth Tampering Through Social Media: Malaysia’s Approach in Fighting Disinformation & Misinformation - Moonyati Mohd Yatid (Center for Southeast Asian Social Studies (CESASS), 2019)
Though poorly defined and highly politicized, the term ‘Fake News’ has beenpopularized by the Trump administration in recent years. Scholars prefer to use terms such as Information Disorder, in particular Disinformation and Misinformation, to discuss this global concern. The dissemination of disinformation and misinformation is not new. However, the penetration of social media and messaging applications today enable such information to spread much faster, deeper and wider. Further, social media and messaging applications have become the public’s source of primary information. These platforms are fast-becoming a birthplace of the manipulation of truth andthe influencing of public opinion. The advancement of technology has alsobeen manipulated to create false information and add to the severity of the problem. The impact of disinformation and misinformation varies: fromfinancial difficulties faced by businesses to influencing the outcome of electionsto physical violence triggered by racial and religious tensions. This paper aims to explore: 1) How information disorder, in particular, disinformation and misinformation, are being disseminated through social media and instantmessaging platforms to influence public opinion; 2)How states respond to disinformation and misinformation; 3) Malaysia’s disinformation andmisinformation landscape and 4) Key areas for Malaysia to improve on, namely enhancing its current legal responses, developing digital literacy, heightening the accountability of social media platforms and strengthening the fact-checking mechanism.